2020
DOI: 10.1080/21695717.2020.1807256
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry as a measure for listening effort in children

Abstract: Purpose Listening effort can be defined as the deliberate allocation of mental resources to overcome obstacles when carrying out a listening task. Requiring mental resources, it may detract from other types of cognitive activities, leading to a general worsening of cognitive performances. The aim of this review is to provide information about how to use pupillometry to explore listening effort in children too and discuss the suitability of this technique when measuring listening effort in this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Using pupil size as an objective measure of listening effort, researchers have uncovered excess effort in individuals with hearing disorders, even when comprehension accuracy is high (e.g., Wagner et al., 2019; Winn & Moore, 2018; Zekveld et al., 2011). Pupillometry has also helped to identify potential solutions to excessive listening effort problems (e.g., through signal processing in hearing aids; Ohlenforst et al., 2017; Wendt et al., 2017) and has given researchers the capability to objectively measure listening effort in children who could experience developmental delays as a result of excessive effort (Gómez‐Merino et al., 2020). Recently, there have been a large number of studies that have used analyses of alpha‐band (~8–13 Hz) power in the M/EEG in a similar vein (Alhanbali et al., 2019; Decruy et al., 2020; Hall et al., 2019; Hunter, 2020; Marsella et al., 2017; McMahon et al., 2016; Miles et al., 2017; Obleser et al., 2012; Petersen et al., 2015; Seifi Ala et al., 2020; Winneke et al., 2020; Wöstmann et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using pupil size as an objective measure of listening effort, researchers have uncovered excess effort in individuals with hearing disorders, even when comprehension accuracy is high (e.g., Wagner et al., 2019; Winn & Moore, 2018; Zekveld et al., 2011). Pupillometry has also helped to identify potential solutions to excessive listening effort problems (e.g., through signal processing in hearing aids; Ohlenforst et al., 2017; Wendt et al., 2017) and has given researchers the capability to objectively measure listening effort in children who could experience developmental delays as a result of excessive effort (Gómez‐Merino et al., 2020). Recently, there have been a large number of studies that have used analyses of alpha‐band (~8–13 Hz) power in the M/EEG in a similar vein (Alhanbali et al., 2019; Decruy et al., 2020; Hall et al., 2019; Hunter, 2020; Marsella et al., 2017; McMahon et al., 2016; Miles et al., 2017; Obleser et al., 2012; Petersen et al., 2015; Seifi Ala et al., 2020; Winneke et al., 2020; Wöstmann et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found evidence of school-age children having to put more effort into listening tasks in background noise than in quiet, or when the level of background noise increased. This greater effort was revealed by slower response times (Lewis et al, 2016;McGarrigle et al, 2019;Prodi et al, 2019a;Prodi et al, 2019b;Picou et al, 2019), and by a larger task-evoked increase in pupil size (Steel et al, 2015;McGarrigle et al, 2017;Gómez-Merino et al, 2020). The results were not entirely consistent across the studies, however, presumably due to a different sensitivity of the listening effort measures (McGarrigle et al, 2017;McGarrigle et al, 2019), and to the children's difficulty in preferentially allocating their attention during dual tasks (Choi et al, 2008;Picou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of the common physiological measures used to index listening effort is pupillometry. This measure examines task-evoked pupillary responses, where increased mean pupil dilation (average magnitude of pupil size observed during the task) and larger peak pupil size (maximum dilation recorded during the task), are associated with higher processing load, indicating increased effort (e.g., Gómez-Merino et al, 2020;Koelewijn et al, 2012Koelewijn et al, , 2014Kramer et al, 2016;Paulus et al, 2020;Silcox & Payne, 2021;van der Wel & van Steenbergen, 2018;Van Engen & McLaughlin, 2018;Wendt et al, 2014;Winn et al, 2015Winn et al, , 2018Zekveld et al, 2018;. In addition to pupillometry, various other physiological techniques have been suggested to capture differences in effort.…”
Section: Introductionmentioning
confidence: 99%